2021
DOI: 10.1021/acsinfecdis.1c00331
|View full text |Cite
|
Sign up to set email alerts
|

The CARB-X Portfolio of Nontraditional Antibacterial Products

Abstract: The growing prevalence of antibiotic-resistant bacterial pathogens and the lack of new medicines to treat the infections they cause remain a significant global threat. In recent years, this ongoing unmet need has encouraged more research groups to focus on the discovery and development of nontraditional antibacterial agents, ranging from anti-virulence strategies to bacteriophage and ways to modulate the microbiome. The Combating Antibiotic-Resistant Bacteria Biopharmaceutical Accelerator (CARB-X) is a global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…These cationic peptides selectively target and attack the anionic membranes of bacterial pathogens 13 , 14 . Encouragingly, a recent update from the CARB-X antibiotic accelerator reports that direct-acting peptides account for approximately 11% of their portfolio, showing renewed industry interest in these compounds to overcome multidrug resistant bacterial strains 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These cationic peptides selectively target and attack the anionic membranes of bacterial pathogens 13 , 14 . Encouragingly, a recent update from the CARB-X antibiotic accelerator reports that direct-acting peptides account for approximately 11% of their portfolio, showing renewed industry interest in these compounds to overcome multidrug resistant bacterial strains 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Renewed focus to identify new antibacterial drugs against MDR bacteria, combined with several recent financing mechanisms, has helped to increase the number of traditional and nontraditional antibacterial agents moving through the preclinical ( 94 ) and clinical development pipelines ( 41 , 90 , 95 , 96 ). Despite a total of 76 antibacterial candidates (45 traditional and 31 nontraditional) being evaluated in clinical trials on 30 June 2021, our analysis indicated that there were still relatively few clinically differentiated antibacterial agents in late-stage clinical development, especially against critical-priority pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that SMEs are facing, with limited capacity, the risks and down-turns of product failure in the early stages, despite the fact that this research stage is the mainstay in R&D, to ensure the sustainability of new antibacterial drug candidates in the development pipeline. The main funding programs are focusing on the pre-clinical stages as a result of private–public partnerships, such as the Global Antibiotic Research and Development Partnership (GARDP), Combating Antibiotic-Resistant Bacteria Biopharmaceutical Accelerator (CARB-X) [ 160 , 237 , 238 ], Innovative Medicines Initiative (IMI), and Drugs for Neglected Diseases Initiative (DNDi), in addition to international as well as national non-profit organizations and government programs [ 12 ]. Multiple incentives are available to boost R&D initiatives, which may or may not be efficient, depending on the context and framework.…”
Section: Antibiotics Research and Development: Incentives And Barriersmentioning
confidence: 99%